Scaleable round trip time estimation for layered multicast protocol - Ghazali, Osman; Hassan, Suhaidi (IEEE Computer Society, 2006)
Layered multicast protocol (LMP) is designed for simultaneous and real-time content distribution to a large number of disparate receivers across a heterogeneous internet.Most LMPs use TCP-equation model to control their rate, which is usually performed at the receivers. The equation models steady-state TCP behaviour with a function of loss rate, round trip time (RTT), timeout, and packet size. Loss rate can be easily estimated at the receivers, however RTT estimation pose implosion problem at the sender in particular when the number of receivers is very large. In this paper, we proposed a new technique for scalable RTT estimation for layered multicast protocol. The technique enables layered multicast receivers to estimate RTT without causing implosion problem to the sender.